Severe Vitamin D Deficiency in Human Immunodeficiency Virus-Infected Pregnant Women is Associated with Preterm Birth - Jao, Jennifer; Freimanis, Laura; Mussi-Pinhata, Marisa M.; Cohen, Rachel A.; Monteiro, Jacqueline Pontes; Cruz, Maria Leticia; Branch, Andrea; Sperling, Rhoda S.; Siberry, George K.; for the NISDI LILAC Protocol (American Journal of Perinatology, 2017)
Background Low maternal vitamin D has been associated with preterm birth (PTB). Human immunodeficiency virus (HIV)-infected pregnant women are at risk for PTB, but data on maternal vitamin D and PTB in this population are scarce.Methods In a cohort of Latin American HIV-infected pregnant women from the National Institute of Child Health and Human Development International Site Development Initiative protocol, we examined the association between maternal vitamin D status and PTB. Vitamin D status was defined as the following 25-hydroxyvitamin D levels: severe deficiency (< 10 ng/mL), deficiency (10–20 ng/mL), insufficiency (21–29 ng/mL), and sufficiency (≥30 ng/mL). PTB was defined as delivery at < 37 weeks' gestational age (GA). Logistic regression was used to assess the association between maternal vitamin D status and PTB.Results Of 715 HIV-infected pregnant women, 13 (1.8%) were severely vitamin D deficient, 224 (31.3%) were deficient, and 233 were (32.6%) insufficient. Overall, 23.2% (166/715) of pregnancies resulted in PTB (median GA of PTBs = 36 weeks [interquartile range: 34–36]). In multivariate analysis, severe vitamin D deficiency was associated with PTB (odds ratio = 4.7, 95% confidence interval: 1.3–16.8]).Conclusion Severe maternal vitamin D deficiency is associated with PTB in HIV-infected Latin American pregnant women. Further studies are warranted to determine if vitamin D supplementation in HIV-infected women may impact PTB.
Keywords: vitamin D; preterm birth; HIV; pregnant women; pregnancy